2020
DOI: 10.1021/acs.jpcb.0c04844
|View full text |Cite
|
Sign up to set email alerts
|

Are There Magic Compositions in Deep Eutectic Solvents? Effects of Composition and Water Content in Choline Chloride/Ethylene Glycol from Ab Initio Molecular Dynamics

Abstract: Ab initio molecular dynamics simulations at elevated temperature are carried out to investigate the microscopic structure of liquid mixtures (deep eutectic solvents) composed of 1:1 and 1:2 choline chloride:ethylene glycol ([Ch]­Cl:EG) and 1:2:1 choline chloride:ethylene glycol:water ([Ch]­Cl:EG:water). In the present study, we aim to understand the composition effect on the choline chloride:ethylene glycol deep eutectic solvent and whether there is a specific composition in these solvents with marked special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 83 publications
(120 reference statements)
15
82
0
Order By: Relevance
“…The interactions between the cation and the HBD are not marked, as shown in Figure 7. These results are in agreement with a recent ab-initio MD study, 72 even though the intensities of certain peaks do not coincide perfectly, as can be expected due to the small sizes and duration sof AIMD trajectories, as well as the obvious differences in the Hamiltonian. good accord between two methods for Cl -• • • Ch + correlations, while the intensity for EG is lower from our force field when compared to AIMD, which could be related to faster diffusion of the HBD discussed above.…”
Section: B Modification Of Atomic Diameterssupporting
confidence: 90%
“…The interactions between the cation and the HBD are not marked, as shown in Figure 7. These results are in agreement with a recent ab-initio MD study, 72 even though the intensities of certain peaks do not coincide perfectly, as can be expected due to the small sizes and duration sof AIMD trajectories, as well as the obvious differences in the Hamiltonian. good accord between two methods for Cl -• • • Ch + correlations, while the intensity for EG is lower from our force field when compared to AIMD, which could be related to faster diffusion of the HBD discussed above.…”
Section: B Modification Of Atomic Diameterssupporting
confidence: 90%
“…The interactions between the cation and the HBD are not marked, as shown in Figure 6. These results are in agreement with a recent ab-initio MD study, 65 even though the intensities of certain peaks do not coincide perfectly. In particular, the height of the first peak Clwith EG is underestimated by the Cl&Pol force field when compared to the AIMD, and this could be related to faster diffusion of the HBD discussed above.…”
Section: The H • • • a Distances And The D H • • • A Angles (Where A supporting
confidence: 88%
“…All the DES used in this work have a higher density than the pure HBD used in their preparation and at a fixed temperature, the density increases with a higher molar fraction of the HBA. Other workers 45,46 have shown that the DES in general exhibit a non ideal behavior. For the systems studied in this work we cannot confirm this finding as the density of solid choline chloride has not been reported in literature and the first derivative of molar volume remains constant over the limited range of mole fractions studied.…”
Section: Density and Viscosity Measurementsmentioning
confidence: 96%